Evaluasi dalam Bimbingan dan Konseling - Hadiwinarto Hadiwinarto; Arsyadani Mishabuddin; Illawaty Sulian (Seminar Konseling 2017, 2017)
This study aims to present a concept on the evaluation results of theoretical studies in guidance and counseling in schools.. Explain the concept of the meaning of the measurement, assessment and evaluation of the meaning. The study starts from the evaluation of the importance of the guidance and counselling services, both as a program or as an activity services. Guidance and counselling services as an integral part of the educational services, should be evaluated. Because it will be used as the main considerations to determine the urgency of guidance and counselling services in schools, especially the urgency on academic and non-academic achievement. The measured judgment is something that is absolutely used. Focus the discussion on how to assess the performance of the guidance and counselling teachers or school counsellors in carrying out four types of services, namely: guidance service of classical, guidance service groups, counseling services group and individual counselling service. Results of the study offers an instrument containing signs abilities and skills guidance counseling teacher or school counselor who must be controlled so that it can be used to assess performance. The fourth assessment skills are also very important for prospective teachers of guidance and counseling.